Analisis Statistik Pengaruh Kenaikan PPN Tahun 2025 Terhadap Harga Permintaan, Kondisi Pasar dan Sosial Ekonomi Indonesia - Rabani, Kayla Fatha; Shofie, Maulaya; Alfarizi, Muhammad Bintang; Hayatul Fazri, Muhammad Haikal; Sutrisna, Muhammad; Wardiyah, Mia Lasmi (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2024)
This study, titled "Analysis of the Statistical Impact of the 2025 Value Added Tax (VAT) Increase on Demand Prices, Market Conditions, and Socioeconomics in Indonesia," employs a literature review methodology based on previous research. The study aims to analyze the impact of the 2025 VAT increase on demand prices, market conditions, and socioeconomic aspects in Indonesia. The results of the study are expected to serve as reading materials, reference materials, and even input for related stakeholders. The study employed a literature review methodology, gathering and analyzing relevant data from existing studies and publications. The data was then used to assess the impact of the VAT increase on demand prices, market conditions, and socioeconomic aspects in Indonesia. The study found that the 2% VAT increase in 2025 had a significant impact on increasing the prices of goods and services across various sectors. This led to a decrease in purchasing power, particularly among low-income groups. Market conditions also experienced a slowdown, with a decline in sales volume and consumption levels. Socioeconomically, the VAT increase contributed to an increase in poverty rates and income inequality in Indonesia. The study concludes that the VAT increase policy needs to be balanced with compensation and incentive programs for low-income earners to minimize its negative impacts. The government also needs to conduct regular evaluations and adjustments to VAT rates to maintain economic stability and public welfare.